2016
DOI: 10.18632/oncotarget.12839
|View full text |Cite
|
Sign up to set email alerts
|

GATA4 promotes hepatoblastoma cell proliferation by altering expression of miR125b and DKK3

Abstract: GATA4 is a zinc finger DNA-binding protein that plays an important role in mammalian liver development. However, the effects of GATA4 in hepatoblastoma (HB), a common liver cancer in pediatric patients, remain largely unknown. In this study, we demonstrate that GATA4 promotes growth and survival in the Huh6 human hepatoblastoma cell line. GATA4 expression was high in Huh6 cells, and its knockdown decreased expression of Dickkopf-related protein 3 (DKK3), a gene that may contribute to premature or undifferentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…Moreover, Fang et al showed that silencing of GATA-6 resulted in decreased the expression of important mediators including MMP-2 and MMP-9 [31]. Also, a previous study has shown that GATA4 promoted oncogenesis through suppression of DKK3 expression in hepatoma cells [32]. MMP-2 and MMP-9 are enzymes involved in prostatic development and growth, important to cancer progression [33].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Fang et al showed that silencing of GATA-6 resulted in decreased the expression of important mediators including MMP-2 and MMP-9 [31]. Also, a previous study has shown that GATA4 promoted oncogenesis through suppression of DKK3 expression in hepatoma cells [32]. MMP-2 and MMP-9 are enzymes involved in prostatic development and growth, important to cancer progression [33].…”
Section: Discussionmentioning
confidence: 99%
“…A recent report suggested that GATA4 may facilitate hepatoblastoma cell proliferation by regulating the expression of DKK3 and microRNA (miRNA) miR125b (40). A number of other studies have also demonstrated that miRNAs and transcription factors are closely correlated in gene regulatory networks (41), and bioinformatics analyses suggested that the promoter sequences of most mammalian miRNA genes included at least one GATA box, which indicated that GATA4 may transcriptionally regulate certain miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…p62, an autophagic cargo protein, binds to endogenous autophagy substrates during autophagic lysosomal degradation. GATA4 acts as an activator of hepatoblastoma cell proliferation [18] ; after binding to p62, GATA4 is degraded through the autophagic lysosomal pathway [19] . Our results showed that p62 binds to c-Myc, causing c-Myc degradation through the lysosomal pathway ( Figure 5), which is consistent with [20] , but they did not discuss AMBRA1 causes the degradation of c-Myc by ubiquitin proteasome pathway or the autophagy-lysosomal pathway.…”
Section: Discussionmentioning
confidence: 99%